The Effect of Perceived Usefulness, Brand Image, and Promotion on Gopay E-Wallet User Loyalty in Semarang City (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the factors influencing GoPay user loyalty in Semarang. The background of this research is based on the high penetration of e-wallet services in Indonesia, which is increasingly competitive, with many service providers such as OVO, DANA, ShopeePay, and LinkAja offering various promotional programs. The research method used a quantitative approach through a survey of 120 active GoPay user respondents, then the data was analyzed using the SmartPLS application. The results showed that promotions did not significantly influence user loyalty, while perceptions of usefulness and brand image had a positive and significant influence. This indicates that user loyalty is not only built through short-term incentives, but is more determined by perceptions of service benefits and trust in the brand image. These findings emphasize the importance of companies not only relying on promotional strategies, but rather focusing more on improving service quality, feature innovation, and consistency in maintaining brand reputation. With the right strategy, GoPay is expected to maintain a loyal user base amidst the increasingly fierce e-wallet competition in Indonesia.